2011
DOI: 10.1123/jpah.8.7.926
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Active Commuting to School and to Work Among Brazilian Adolescents

Abstract: The proportion of students taking active trips was higher when going to work than to school. All indicators were associated with the mode of commuting, except gender and place of residence for commuting to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 19 publications
1
23
1
7
Order By: Relevance
“…Overall, individual correlates of active commuting are also similar across countries [5][6][7][8] . For instance, age, income and the number of perceived barriers are with less active community in both high and low-to-middle income countries 9 .…”
Section: Barriers For Active Commuting To Schoolmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, individual correlates of active commuting are also similar across countries [5][6][7][8] . For instance, age, income and the number of perceived barriers are with less active community in both high and low-to-middle income countries 9 .…”
Section: Barriers For Active Commuting To Schoolmentioning
confidence: 80%
“…In high-income countries, as United States, Canada and Belgium, the prevalence of active commuting ranges from 50-68% 2-4 whereas in Brazil, despite the limited evidence, the prevalence is somehow similar to high-income countries (49-63%) 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents from rural areas were less likely to walk or cycle to school (Sabey et al, 2009;Silva et al, 2011;Wong et aL, 2011 ) pre sumably because of lower school density in rural areas and thus greater distances from an adolescent's home to school Distance from home to school is the most common bar rier to active commut ing to school because it is the primary factor in the parents' decision making process for or against allowing their child to walk or cycle to school (Sirard and Slater, 2008) because it is not feasible to walk or cycle to school if the distance is too far (Nelson et al, 2008;Sirard Distribution of different modes of commuting to school by sodo-dernographic variables for adolescents in Germany, 2003 Boys ( n=938 and Slater, 2008) a reasonable walking and biking distance of Bel gium older adolescents are 2.0 km and 8.0 km, respectively (Van Dyck et aL, 201 0 ). However, the distance from home to school is difficult to measure especially in large scale studies (Chillon et al, 2009; Table S and Gauvin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Gender (Bungum et al, 2009;Chillon et al, 2010;Larsen et al, 2009;Pabayo and Gauvin, 2008), socioeco nomic variables such as parental education (Chillon et al, 2009;Shi et al, 2006), income (Babey et al, 2009;Pabayo et al, 2011;Pont et al, 2009;Tudor Locke et al, 2003) and the social, physical (Kerr et al, 2006;Nelson et al, 2008) and residential (Silva et al, 2011;Wong et al, 2011) environments affect commuting behaviour. Espe cially, distance from home to school is a strong barrier of active com muting to school because walking or biking long distances is not feasible (Van Dyck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (43) found that Brazilian adolescents of higher economic levels had a higher prevalence of passive displacement to school than those from lower economic levels. In addition, greater purchasing power can contribute to more time in sedentary activities, which in turn reduces the time spent on leisure activities, since sedentary behavior is also associated with higher maternal education and higher economic level in this population.…”
Section: Brazilian Healthy Eating Index Revised (Bhei-r)mentioning
confidence: 99%